An Integrated Smart Sensor Dressing for Real-Time Wound Microenvironment Monitoring and Promoting Angiogenesis and Wound Healing - Zhang, Yuheng; Li, Tian; Zhao, Congying; Li, Jinqing; Huang, Rong; Zhang, Qianru; Li, Yongqian; Li, Xueyong (Frontiers in Cell and Developmental Biology, 2021)
Prolonged chronic wounds not only place great pressure on patients but also increase the medical burden. The emergence of tissue engineering dressings has fortunately brought good news to these patients. Recently, the relationship between the wound microenvironment and wound healing has been gradually clarified. Therefore, the state of wounds can be roughly ascertained by monitoring the microenvironment in real time. Here, we designed a three-layer integrated smart dressing, including a biomimetic nanofibre membrane, microenvironment sensor and β-cyclodextrin-containing gelatine methacryloyl (GelMA+β-cd) UV-crosslinked hydrogel. The hydrogel helped increase the expression of vascular endothelial growth factor (VEGF) through hypoxia-inducible factor-1α (HIF-1α) to promote neovascularization and wound healing. The microenvironment sensors, combined with biological dressings, still exhibited satisfactory measurement accuracy, stability, durability and biocompatibility. A BLE4.0 antenna was used to receive, display and upload wound microenvironment data in real time. Such integrated smart dressings can not only achieve biological functions but also monitor changes in the wound microenvironment in real time. This application can overcome the "unknown" state during the process of wound healing and provide support for clinical work.